Diagnóstico Educativo acerca do consumo de carne comercializada em São Luís – MA – Um olhar dos escolares da EJA - Goulart , Goulart, Flávia Karina Lima Anceles (2014)
Health Education as an educational practice teaches the population or specific groups how to acquire hygienic habits that promote health and avoid disease. Thus, an Educational Diagnosis was conducted about the consumption of meat sold in São Luís - MA in order to trace the socioeconomic, cultural and behavioral profile of students, teachers and school managers of Young and Adults Education to subsidize a Health Education Program about the importance of eating quality meat. The research was a descriptive, qualitative and quantitative study, developed in 7 public schools in São Luís - MA. The data collected through structured questionnaires determined the profile public of Young and Adult Education and the level of knowledge about aspects related to the consumption of quality meat. The sampling design considered a finite population of 479 students, with probability sampling method and sample size determination based on the method of Luchesa (2011), with confidence level of 95.00% (z = 1.96) and margin of error of 0.05 (5.00%). Thus, the research was based on 263 questionnaires answered, 82% by students, 15% by faculty, and 3% by managers as meat consumers. The socioeconomic and cultural profile of the students showed a prevalence of: female gender (83%); age between 19 and 30 years old (41%), and family income lower than 1 minimum wage (27%). The profile of the group of teachers and managers showed that 3% declared an income above 6 minimum wages. Despite the different educational level between these 2 distinct groups (students and teachers/managers), the findings about the choice of place to buy meat revealed 43% in markets and butcher shops, and another 43% in open markets for both groups. Regarding the knowledge about the seals of the municipal inspection service, only 6% of the teachers and managers group associated them with sanitary inspection, while 95% of the students did not know about the seals. About the diseases transmitted by meat, 63% were unaware of them and have an erroneous cultural practice of "washing the meat before preparing it for consumption". We conclude that there is a lack of sanitary information regarding the quality of meat and the diseases transmitted by consumption without inspection, making the risk to public health high. The lack of information is enhanced by behaviors related to consumer preference for buying meat without refrigeration, reflecting cultural aspects of the reality of São Luís, being necessary the proposition of the Health Education Program in schools in order to make consumers more demanding, contributing to an improvement in public health